1991
DOI: 10.1111/j.1476-5381.1991.tb12301.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the 5‐hydroxytryptamine receptor mediating smooth muscle relaxation in the rat oesophagus

Abstract: 1 An investigation has been made into the 5-hydroxytryptamine (5-HT) receptor mediating relaxation of rat oesophagus in preparations precontracted with carbachol.2 In tissues treated with pargyline (100pM) and in the presence of corticosterone (30OUM) and cocaine (30 pM) the potency of 5-HT and 5-methoxytyramine (5-MeOT) was not changed but the maximum response to these agonists was reduced. Thus there was no evidence of metabolism and/or uptake through an amine depleting mechanism. 3 The relaxant concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 11 publications
7
44
0
Order By: Relevance
“…The use of the enantiomers of zacopride has indicated small but significant differences in the affinities of R-and S-zacopride for the [3H]-GR1 13808 binding site in homogenates of both guinea-pig hippocampus and striatum (P = 0.01 and 0.04 respectively). This compares well with functional data in guinea-pig ileum where S-zacopride has been shown to be a full agonist and R-zacopride a weak partial agonist (Eglen et al, 1990 (Dumuis et al, 1988;Craig & Clarke, 1990;Eglen et al, 1990;Elswood et al, 1991;Reeves et al, 1991) in both the guinea-pig hippocampus and the striatum pK1 (Grossman et al, 1993). Hill coefficients for 5-HT are slightly increased by the addition of GTP, however, values obtained both in the presence and absence of GTP are not significantly different from unity.…”
Section: Establishment Of Suitable Preparationsupporting
confidence: 72%
See 2 more Smart Citations
“…The use of the enantiomers of zacopride has indicated small but significant differences in the affinities of R-and S-zacopride for the [3H]-GR1 13808 binding site in homogenates of both guinea-pig hippocampus and striatum (P = 0.01 and 0.04 respectively). This compares well with functional data in guinea-pig ileum where S-zacopride has been shown to be a full agonist and R-zacopride a weak partial agonist (Eglen et al, 1990 (Dumuis et al, 1988;Craig & Clarke, 1990;Eglen et al, 1990;Elswood et al, 1991;Reeves et al, 1991) in both the guinea-pig hippocampus and the striatum pK1 (Grossman et al, 1993). Hill coefficients for 5-HT are slightly increased by the addition of GTP, however, values obtained both in the presence and absence of GTP are not significantly different from unity.…”
Section: Establishment Of Suitable Preparationsupporting
confidence: 72%
“…In functional studies in rat oesophagus and guinea-pig colon, renzapride and R,S-zacopride have very similar acitivity with renzapride being fractionally more potent (Reeves et al, 1991;Elswood et al, 1991). In the present binding study, renzapride also revealed a slightly higher affinity than R,Szacopride (pKi = 7.0 and 6.8 respectively in the striatum and 6.9 and 6.7 in the hippocampus).…”
Section: Establishment Of Suitable Preparationsupporting
confidence: 49%
See 1 more Smart Citation
“…In the gastrointestinal tract, the 5-HT4 receptor has been identified at neuronal sites of the guinea-pig ileum (Craig & Clarke, 1990) and colon (Elswood et al, 1991;Wardle & Sanger, 1993) and at non-neuronal sites in rat oesophagus (Reeves et al, 1991;Baxter et al, 1991) and terminal ileum (Tuladhar et al, 1991a). In preparations from the guinea-pig, activation of these receptors results in a contractile response while in those from the rat, relaxation.…”
mentioning
confidence: 99%
“…Additionally, substituted benzamides, including renzapride, cisapride, zacopride and metoclopramide, which are 5-HT3 receptor antagonists, are agonists at the 5-HT4 receptor. Further characterization of 5-HT4 receptors is by the weak antagonistic effect of tropisetron with pKB 5.8-6.7 (Baxter et al, 1991;Reeves et al, 1991), although this compound is a potent 5-HT3 receptor antagonist, pKB 7.8-10.6 (Richardson et al, 1985). The 5-HT4 receptor is also antagonized by DAU 6285 (Bockaert et al, 1992) and GR 113808 (Grossman et Author for correspondence.…”
mentioning
confidence: 99%